A Philosophy of Schooling Care and Curiosity in Community - Stern, Julian (Springer International Publishing, 2018)
This book provides an optimistic account of the value and role of schooling. Schooling is a common but not universal approach to education and has need of its own distinctive justification, in contrast to other approaches such as home-based or work-based education. The book tackles and rejects the various large-scale 'functional' theories of schooling which continue to dominate current debates and policies, such as schooling supporting employment and the economy, or developing citizenship. Instead, it argues that schooling and schools should be viewed as places to learn community within and through community. The lived reality of relationships within schools, based on care and curiosity, is as strong as ever: and upon this foundation is built an original philosophy of schooling. This reflective book will appeal to students and scholars of philosophy of education and to all professionals concerned with schools.